Studies on B- and T-cell receptors for lysozyme. - Charreire, J (1975)
BALB/c mice have been immunized by intravenous administration of native or reduced and alkylated lysozyme. Primary immune response to these antigens was studied at the humoral level (by the Farr assay) and at the cellular level (by the rosette and the plaque assays using lysozyme coupled to sheep or pigeon erythrocytes). Antibodies and theta-negative RFC were specific for the antigen used for immunization. Specific inhibition of theta-negative RFC after incubation with the soluble immunizing antigen confirmed this specificity. Conversely, most theta-positive RFC had double specificity both to native and denatured lysozyme and showed lower avidity for the immunizing antigen, as shown by inhibition studies with soluble antigen. These data suggest that T cells have a broader specificity for lysozyme than B cells and also that, in this particular system, cytophilic antibodies are probably not responsible for the formation of theta-positive rosettes.